2020
DOI: 10.1155/2020/9381506
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis Exploring Taxonomic and Functional Diversity of Soil Microbial Communities in Sugarcane Fields Applied with Organic Fertilizer

Abstract: Organic fertilizers are critically important to soil fertility, microbial communities, and sustainable agricultural strategies. We compared the effect of two fertilizer groups (organic+chemical fertilizer: OM, chemical fertilizer: CK) on sugarcane growth, by observing the difference in microbial communities and functions, soil nutrient status, and agronomic characters of sugarcane. The results showed that the sugar content and yield of sugarcane increased significantly under organic fertilizer treatment. We be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
(51 reference statements)
3
9
0
Order By: Relevance
“…However, fertilizer concentrations significantly affect the germination percentage and need to be adjusted to optimum levels. The percentage of germinated seeds is in accordance with results described by other authors, who mention that organic fertilizers are nutritional supplements that improve the yield and growth of agricultural crops ( Gómez-Álvarez et al, 2008 ; Li et al, 2020 ). The reason for this is the increase in the availability of nutrients that are not easily assimilated by the plant under natural conditions and thus improve soil degradation.…”
Section: Discussionsupporting
confidence: 90%
“…However, fertilizer concentrations significantly affect the germination percentage and need to be adjusted to optimum levels. The percentage of germinated seeds is in accordance with results described by other authors, who mention that organic fertilizers are nutritional supplements that improve the yield and growth of agricultural crops ( Gómez-Álvarez et al, 2008 ; Li et al, 2020 ). The reason for this is the increase in the availability of nutrients that are not easily assimilated by the plant under natural conditions and thus improve soil degradation.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, 27 substances were increased by OF but not CF, including arabitol, threitol, inosine, glycerol, oleic acid, palmitic acid, dodecanol, thymine, 2-hydroxyvaleric acid, xylose, glucose-1-phosphate, glutaric acid, N-acetyl-D-hexosamine, deoxycholic acid, zymosterol, threonic acid, guanidinosuccinate, 2' -deoxyguanosine, citraconic acid, vanillic acid, glucosamine, phthalic acid, phytanic acid, inulotriose, inositol-4-monophosphate, malonic acid, and adipic acid were significantly increased (Table 7). In agreement with the result of this study, the application of bioorganic fertilizer caused the increase in the relative content of glucoheptulose, palmitic acid, phytanic acid, and deoxycholic acid [56,57]. Among the metabolites, inosine is reported to be essential for the growth of plants, which is involved in phosphatidylinositol signal transduction, auxin storage and transportation, phytic acid biosynthesis, cell wall biosynthesis and plant response to stress [58], and it can protect the cell membrane system by reducing the damage of membrane lipid peroxidation and enhancing the activity of antioxidant enzymes [34,54].…”
Section: The Effect Of Compound/bio-organic Fertilizer On Rhizosphere Soil Metabolomicssupporting
confidence: 92%
“…Liu et al ( 2021 ) found that intercropping alfalfa with oat provided rich nutrients for soil microorganisms and ultimately affected the change of soil microbial dominant population and quantity due to the litter and root exudates. A higher soil microbial diversity index is more conducive to improving the stability and resistance of soil ecosystems, ensuring the normal operation of soil ecosystem function (Li et al, 2020b ). The α-diversity indices, including Chao1 and ACE, reflected the richness of the soil bacterial community, and the Shannon index reflected the evenness of soil bacterial community, which was positively correlated with the diversity of the soil bacterial community (Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%